"Una muchacha, a quien crío para condesa": El personaje de Sanchica en el segundo Quijote cervantino - Altamirano, Magdalena (El Colegio de México, 2023)
This article analyzes the significance of Sancho Panza’s daugh-ter in the second part of Cervantes’s Quixote and concludes she is essential for the development of certain traits of character displayed by Sancho and Teresa, noticeably their disproportionate yearnings to rise in society. Due to her hypothetical marriage to a nobleman, Sanchica is key to Sancho’s social aspirations; Sanchica’s clothing and activities allow the Duchess to amplify her mockery; they also help the reversion of the farce orchestrated by the Duchess. In addition, Sanchica sheds light on the situation in which peasant women found themselves in early modern Spain.